Poor Respiratory Health is a Consequence of Dhaka's Polluted Air: A Bangladeshi Perspective - Trishul Basak Dibya; Amrin Yeasin Proma; Syed Masudur Rahman Dewan (SAGE Publishing, 2023)
Dhaka, which is the capital and largest metropolis of Bangladesh, has seen an increase in the number of documented cases of respiratory disorders. Every day in Dhaka city, a remarkable number of patients are being diagnosed with poor respiratory conditions. The majority of these patients have no other severe disease history and mostly need to be exposed to outdoor air to meet their occupational requirements, indicating that the ailment may be associated with polluted air. As this is the most pressing issue that must be addressed in order to safeguard public health, we have made an effort to focus on the current situation surrounding the sources of air pollution in the city. Since this is a viewpoint article, we gathered data from various published articles, national dailies, and international reports generated by WHO, CDC, BBC, or other environmental news/report portals to highlight the public health issue related to respiratory health. Poor respiratory health is one of the main consequences of Dhaka's contaminated air, as determined by our analysis.